Metacognitive Skills Level among English ‎Language Teachers’ in Ma’an Governorate in ‎the Light of Number of Variables - AL-Ghazo, Khitam (Jordan Journal of Educational Sciences, 2023)
The study aimed to reveal the level of English language teachers’ use of metacognitive skills while teaching. The study sample consisted of 141 teachers to whom the MAIT scale was applied (Balcikanli, 2011). The results showed that the level of teachers’ use of metacognitive skills was 3.23. Regarding the dimensions, the mean averages were distributed as follows: the monitoring dimension had a low level mean of 2.39, the evaluation dimension had an average mean of 3.22, and the planning dimension had a high level mean of 3.80. The results also revealed that there was no difference in the mean averages of the English language teachers’ ratings on the instrument as a whole due to gender, that there were differences in the mean averages of the English language teachers’ ratings on the instrument as a whole due to the years of experience and in favor of those (from 10 years and more), and that there were no differences on each dimension of the instrument due to the study variables